Pattern Analysis of Goals Scored in Malaysia Super League 2015 - Nazim Razali; Aida Mustapha; Filipe Manuel Clemente; Md Fauzi Ahmad; Mohamad Aizi Salamat (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper is set to study the pattern of goals scored across 132 matches in 2015 Malaysian Super League (MSL). Despite of well-known researches in European football, no information in Malaysian football teams has been done consistently. To identify the patterns, this research focuses on goals scored based on timing that includes scoring frequency, the impact of first goal achieved by team towards the final match outcome, as well as the impact of having home advantage for matches during MSL 2015.  The findings of this paper will provide useful information on MSL besides helping coaches with fresh insight for creating effective training and tactical plan as the time progressed during match. At the same time, players will also be more prepared for a consistent performance especially when training for matches as the visiting teams.